Evaluation of Integrated Pest Management Strategies for Pod Borer Complex in Redgram - Shaila, O.; Rajashekhar, Mandla; Reddy, T. Prabhakar; Rajashekar, B.; Shankar, A.; Ramakrishna, M.; Jyoshna, E.; Priyanka, N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Pod borers complex is the major biotic constraint occurs during the reproductive phase of the crop accounting 30 to 100% yield losses. Continuous chemical use may result in the development of resistance, resurgence, and secondary pest outbreaks; therefore, management of the pod borer complex with the aid of IPM practices aids in the effective control of pests. KVK, Palem has demonstrated the Integrated Pest Management Strategies for Pod Borer Complex in Redgram in various farmer’s fields of Nagarkurnool District. The results revealed that IPM implementation led to substantial reductions in pod borer complex infestation. Pheromone based monitoring showed a consistent reduction in adult moth populations of gram pod borer in three consecutive weeks at critical stages of the crop i.e., flowering to pod setting stages. There was a significant reduction in per cent incidence of pod borer complex i.e., the spotted pod borer (11.58%), gram pod borer (12.64%), and pod fly (12.68%), was much lower in technology demonstrated fields than the farmer’s practice (21. 98%, 20.04 and 20.38%). Technological and extension gaps were analysed, showcasing farmers' adoption and implementation levels of IPM strategies. The adoption of IPM led to increased redgram yields (34.78%), additional net returns (Rs. 12,500/- per ha) with favourable benefit cost ratio (2.2:1) over farmer’s practice. Further, the farmers can be able to avoid two harmful sprays and can save an amount of Rs. 3500/- per ha. The technology has been disseminated in an area of 450 acres in adopted villages and 1750 acres in the entire Nagarkurnool district by various extension aids.